자기애성향과 공격성의 관계에서 인지적 정서조절전략의 매개효과 - 서수균; Sugyun Seo; 이현두; Hyundu Lee (인간이해, 2018)
본 연구는 자기애성향과 공격성의 관계에서 인지적 정서조절전략이 매개하는지, 자기애성향에 따라 인지적 정서조절전략과 공격성에 차이가 있는지를 알아보고자 하였다. 355명의 대학생을 대상으로 자기애 성격장애 척도, 내현적 자기애 척도, 인지적 정서조절전략 질문지, 공격성 척도를 실시하였다. 자기애성향에 따라 공격성과의 관계를 인지적 정서조절전략이 매개하는지 분석하였으며 외현적 자기애집단, 내현적 자기애집단, 통제집단을 구분하여 변인 간 차이를 확인하였다. 주요 결과는 다음과 같다. 1) 외현적, 내현적 자기애성향과 공격성의 관계에서 부적응적 인지적 정서조절전략만이 부분매개 하였다. 2) 외현적 자기애집단은 통제집단보다 적응적인 전략을 많이 사용하였으며 내현적 자기애집단, 외현적 자기애집단, 통제집단 순으로 부적응적인 전략을 많이 사용하였다. 3) 자기애집단이 통제집단보다 공격성이 높았다. 4) 자기애성향에 따라 인지적 정서조절전략이 공격성에 미치는 영향에 차이가 있었다. 이상의 결과들은 자기애성향자의 공격성을 다루는데 있어서 부적응적인 인지적 정서조절전략 사용을 줄이는 방법이 보다 효과적일 수 있으며 드러나는 공격성 특성에 따라 보다 적합한 전략이 있음을 시사한다. This study examines the mediating effect of cognitive-emotional regulation strategies on the aggression of narcissistic individuals, as well as the differences in emotional regulation strategies and aggression between covert and overt narcissists. The subjects were 355 undergraduate students recruited from the Busan city. They were asked to complete the questionnaires of Narcissistic Personality Disorder Scale, Covert Narcissism Scale, Cognitive Emotion Regulation Questionnaire, and Aggressin Questionnaire-Korean version. The major finding of this study can be summarized as follows. First, maladaptive cognitive-emotional regulation strategies showed the statistically significant partial mediation effect between narcissism disposition types and aggression. However, adaptive emotional regulation strategy did not have meaningful mediated effects. Second, groups with higher narcissistic utilized more maladaptive strategies than the control group. More maladaptive strategies were also displayed by covert narcissistic group compared to overt narcissistic group. And overt narcissism group utilized more adaptive strategies than other groups. Third, the narcissistic groups showed a significantly higher level of aggression than the control group. Finally, cognitive-emotional regulation strategies had a different effect on aggression, depending on narcissistic disposition. The results of this study suggest that differences exist in cognitive-emotional regulation strategies and aggression depending on narcissistic disposition. In addition, the aggression in narcissistic disposition was influenced more by the use of maladaptive emotional regulation strategies than by use of adaptive emotional regulation strategies.